Observations of the Wire Destruction and Plasma Channel Reestablishment Process During the Initial Stage of Triggered Lightning - Shulei Li; Shi Qiu; Lihua Shi; Yun Li; Wansheng Dong (Geophysical Research Letters)
Abstract The wire destruction and plasma channel reestablishment process during the initial stage of a triggered lightning is analyzed based on comprehensive observations, including very high frequency (VHF) mapping array, electric‐magnetic field, and high‐speed video. The detailed discharge processes in both the attempted reconnection process and reconnection process are firstly evidenced by VHF mapping results. The reconnection process is similar to a leader/return‐stroke sequence, while the attempted reconnection process involves more complicated discharges. It is shown that several segments of the wire are fused firstly due to inhomogeneity of the wire, resulting in a series of wire residues. Thereafter, downward extending VHF breakdowns dispersed over hundreds of meters in altitude followed by a recoil‐like event, both of which emitted fairly weak VHF radiation, and no detectable LF electromagnetic field change was observed. It is indicated that there are no significant current flowing or charges movement during the attempted reconnection process.